(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Freight transport and the work of the entire national economy are more closely connected than the connection between passenger transport and other sectors of the national economy, since the formation and increase of tariffs for passenger transportation does not affect the overall dynamics of GDP. In contrast to passenger transport, the demand of the population has little influence on the dynamics of growth in demand for freight transport services - it accounts for less than 4% of gross income from freight transportation. The bulk of business services in the freight industry comes from its three main industries - road, rail and aviation (as a result, they account for 89% of all transport revenues)